A consensus on critical success factors for Enterprise Resource Planning Systems implementation : the experience of Malaysian firms. - Jafari, Seyed Mohammadbagher; Osman, Mohd Rasid; Mohd Yusoff, Rosnah; Tang, Sai Hong (Inderscience, 2009)
Enterprise Resource Planning (ERP) systems can be considered as the most important development in the corporate use of information technology (IT) and are beginning to be the backbone of organisations. The difficulties and high failure rate in implementing ERP systems have been widely cited in the literature. Factors affecting ERP implementation are complex and abundant and numerous authors have identified a variety of factors that can be considered to be critical to the success of an ERP implementation. This paper is an attempt to build a consensus agreement from previous researches about ERP Critical Success Factors (CSFs). Through a comprehensive review of the literature, 10 factors were found to be critical to ERP implementation success. The importance of these factors was investigated within Malaysian companies using questionnaire survey method. The survey results showed a high agreement on the identified CSFs and supported this study's literature findings.